Sustainability and role of plant-based diets in chronic kidney disease prevention and treatment - Marrone, Giulia; Di Lauro, Manuela; Cornali, Kevin; Masci, Claudia; Vanni, Gianluca; Vita, Chiara; Noce, Annalisa (Frontiers in Pharmacology, 2025)
Chronic kidney disease (CKD) affects 10% of the world’s population (namely, 800 million of people) and an increase in CKD prevalence has been observed over the years. This phenomenon in developed countries is related to the spread of chronic degenerative non-communicable diseases (CDNCDs), such as diabetes mellitus, arterial hypertension, obesity, etc., while in low-income to middle-income countries, the CKD prevalence is attributable not only to CDNCDs, but also to infection conditions (like HIV, hepatitis, etc.). Another important difference lies in the age of onset of CKD, which is about 20 years lower in developing countries compared to developed ones. Therefore, CKD is becoming a public health problem, requiring preventive and treatment strategies to counteract its spread and to slow its progression. Moreover, the healthcare costs for the CKD management increase as the disease progresses. In this regard, the approach to prevent and reduce the CKD progression involves pharmacological and nutritional treatments (like Mediterranean Diet, MedRen diet, Flexitarian Diet, Vegetarian Diet and Plant-dominant Low Protein Diet) in order to improve the patients’ quality of life and, at the same time, promote the environmental sustainability. Recent studies have highlighted the benefits of these diets not only for individuals, but also for environment. In particular, plant-based diets have increasingly gained an important role in the prevention and management of chronic diseases, including CKD. In fact, recent scientific studies have highlighted how a greater adherence to predominantly plant-based diets, is associated with a lower risk in developing CKD and also in slowing its progression. With regard to environmental sustainability, it is known how our food choices influence the climate crisis, since the food sector contributes for the 25% to the greenhouse gas emissions. Therefore, to reduce the consumption of animal proteins and to replace them with plant-based proteins are key strategies for sustainability and health, also supported by the European policies. In this context, food industries are starting to increase the offer of plant-based products that have similar characteristics, both sensorial and nutritional, to those of animal origin. This innovation, in fact, presents difficulties due to the perception of taste and the organoleptic appearance of these products. An additional challenge concerns the resistance of the traditional food industry and the lack of awareness of the consumer. The paradigm shift is dictated by the obtained benefits for health and for environment. Life cycle assessment studies have compared the land footprint, carbon footprint and blue water footprint of plant-based products with those of animal origin and pointed out the lower environmental impact of the former. In conclusion, the adoption of sustainable food models will slow down the spread of CDNCDs, such as CKD, positively impacting both on human health and on planet, significantly reducing the costs and resources of the National Health Systems, since they absorb up to 70%–80% of the healthcare costs.